DEVELOPMENT OF E-MODUL FLIPBOOK BUFFER SOLUTION BASED ON DISCOVERY LEARNING MODEL - Syamriani, Syamriani; Jusniar, Jusniar; Hardin, Hardin (Universitas Negeri Surabaya, 2023)
This research and development aim to produce a valid, practical, and effective e-module buffer solution flipbook. The development of this e-module refers to the ADDIE development model which includes the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. There are four subjects in this research, namely media experts and material experts as validity test subjects, chemistry teachers as the practicality test subject,ct, and 35 students in class XI MIPA 3 as the practicality and effectiveness tests subjects. The instruments used for validity are validation sheets by media experts and material experts, practicality, namely observation sheets on the implementation of e-module, teacher and student response questionnaires, and effectiveness, namely learning outcomes tests. The results of this study are: (1) the validity of the digital module from the material expert is 3,6 and the media expert is 3,5 which is in the very valid category with a consistency test between validators are 100% which is in very high criteria, (2) the average percentage of e-module practicality is 85,66%, where the percentage of practicality based on the questionnaire responses of students and teachers the to the digital issue is 85,33% and 86% in the very practical category, 3) e[1]module meet the effective criteria (≥85%) based on the achievement of class completeness with percentage 88,57%. Based on these data, it is concluded that the e-module flipbook buffer solution developed with the ADDIE model is valid, practical, and effective for use in learning.